2000
DOI: 10.1037/0012-1649.36.5.571
|View full text |Cite
|
Sign up to set email alerts
|

The role of comparison in the extension of novel adjectives.

Abstract: Previous reseach has documented that basic-level object categories provide an initial foundation for mapping adjectives to object properties. Children ranging from 21 months to 3 years can successfully extend a novel adjective (e.g., transparent) to other objects sharing a salient property if the objects are all members of the same basic-level category; if the objects are members of different basic-level categories, they fail to extend adjectives systematically (R. S. Klibanoff & S. R. Waxman, 2000a; S. R. Wax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 45 publications
6
106
0
1
Order By: Relevance
“…Though somewhat unsatisfying, this may be interpreted to support previous findings for both consistency (e.g. Brown, 2008 ;Waxman & Klibanoff, 2000) and contextual diversity (Hills et al, 2010). Future research will be needed to disentangle these variables.…”
Section: R E S U L T Ssupporting
confidence: 78%
See 1 more Smart Citation
“…Though somewhat unsatisfying, this may be interpreted to support previous findings for both consistency (e.g. Brown, 2008 ;Waxman & Klibanoff, 2000) and contextual diversity (Hills et al, 2010). Future research will be needed to disentangle these variables.…”
Section: R E S U L T Ssupporting
confidence: 78%
“…low contextual diversity) across contexts has been shown to play an important role for learning verbs and adjectives (e.g. Brown, 2008 ;Waxman & Klibanoff, 2000). In principle, consistency may facilitate word learning among other word classes as well.…”
Section: University Of Warwickmentioning
confidence: 99%
“…Waxman and Klibanoff (2000; found that preschool children who first extended novel adjectives from a standard to highly similar items subsequently performed better than a baseline group at extending the adjectives to less similar items from a different category. Namy (1999, 2002) found that 4-year-olds who were given two highly similar standards (such as an apple and an orange) and encouraged to compare them were likely to extend a new noun label according to taxonomic category instead of to perceptual appearance (e.g., choosing a banana instead of a round balloon); in contrast, children who heard the new label applied to only one of the standards (just the orange) generally chose the perceptual match (the balloon).…”
Section: Methodsmentioning
confidence: 99%
“…This in turn increases the likelihood that the child will subsequently be able to align the early examples with a further, less surface-similar instance of the same relational structure. Many studies have borne out these predictions (Gentner et al in press;Gentner et al 2007;Kotovsky and Gentner 1996;Loewenstein and Gentner 2001;Namy and Gentner 2002;Thompson and Opfer, in press;Waxman and Klibanoff 2000). We exemplify progressive alignment below.…”
Section: How Analogical Processing Fosters Learningmentioning
confidence: 99%